Comparison of various bismuth film electrodes in simultaneous electrochemical detection of heavy metals for application in quantum dot-linked immunoassays - Sýs, Milan; Metelka, Radovan; Korecká, Lucie; Pokorná, Helena; Švancara, Ivan (My University, 2017)
Various electrode materials commonly used in electroanalysis were tested in preparation of respective bismuth film electrodes and compared in simultaneous electrochemical detection of heavy metals, simulating dissolved quantum dots used as labels of antibodies in quantum dot-linked immunosorbent assays. According to results obtained during voltammetric measurements, it can be concluded that selected commercial screen-printed electrodes showed many significant drawbacks which are described in detail. Contrary to the gold disk electrode, conventional glassy carbon electrode coated with thin bismuth film was applicable up to -1.5 V without the need to use very high content of bismuth in supporting electrolyte. Moreover, significant interactions among present metals were observed during their electrochemical stripping analysis, especially in presence of copper and silver.
Srovnání různých bizmutových filmových elektrod při simultánní elektrochemické detekci těžkých kovů pro aplikaci v kvantových tečkových imunoanalýzách
Keywords: Bismuth film electrodes; Electrochemical immunoassays; Heavy metals; Quantum dots; Square wave anodic stripping voltammetry; Bizmutové filmové elektrody; Elektrochemické imunotesty; Těžké kovy; Kvantové tečky; Square wave rozpouštěcí voltammetrie